2004
DOI: 10.1016/j.matprotec.2003.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of design and process parameters on service life of nut hot forging die

Abstract: A nut hot forging die was investigated in order to increase its life time. In a first step forging process simulation shows that die surface temperature reaches 450 • C and that mechanical loads on the die are closely related to the accuracy of the initial billet length. In a second step die thermo-mechanical simulation was used to optimize the design: geometrical aspect as well as shrink fitting were investigated. Life time increase was estimated in using the Manson universal slope relation. This increase was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Concentration of stress in the blades and corners is the reason of this phenomenon. (Garat et al, 2004) obtains identical results as this study showed the concentration of stress in the corners. (Feng and Luo, 2000) showed that stress increased during the forging process and also showed this by the moving forward of the die.…”
Section: Resultssupporting
confidence: 83%
“…Concentration of stress in the blades and corners is the reason of this phenomenon. (Garat et al, 2004) obtains identical results as this study showed the concentration of stress in the corners. (Feng and Luo, 2000) showed that stress increased during the forging process and also showed this by the moving forward of the die.…”
Section: Resultssupporting
confidence: 83%
“…Optimised numerical tool design can take into account the process variables that occur in the manufacturing process [9] and enable a more efficient design of the tools and step sequences. As a result, an optimisation of the tool configuration is already possible in the construction phase of the forging process through stress-adapted dimensioning with little experimental effort for process design [10].…”
Section: Introductionmentioning
confidence: 99%
“…Finite element method was also used to ponder nut forging die in order to increase die fatigue life. The research results compared the effect of initial billet length and temperature decrease on the forging force to conclude that the former factor is more important (Garat et al, 2004). Tomov et al (2004) studied closed forging die using numerical analysis and used finite element method for suggesting a proper design for flash dimension with consideration of flash geometry effects on the parameter process.…”
Section: Introductionmentioning
confidence: 99%